In-Silico Design of an E2 Envelope Glycoprotein targeted Multi Epitope vaccine against Chikungunya Virus (CHIKV) - Ahmed, Intizar (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.